A cross-sectional study of fall injuries in senior people attending emergency ward in BPKIHS, a tertiary level hospital, Dharan, eastern region of Nepal - Rai, Bijendra Kumar; Chaudhari, R; Yadav, A; Rai, B (Health Renaissance, 2017)
Background: The Senior or elderly population is rapidly growing in Nepal. They sustain injuries fall frequently which is mostly unintentional and occurs either inside or outside of house. The cost of treatment is high. The most effective fall prevention strategies are multifactorial interventions targeting identified risk factors, exercises for muscle strengthening combined with balance training and withdrawal of psychotropic medication. Objective: To study the pattern and associated rule factors of fall injuries among elderly patients from frequenting in the emergency. Method: It is an observational cross sectional study of fall in senior people presenting in emergency ward using a semi-structured questionnaire. Result: Male and female subjects were 76 (54.3%) and 64 (45.7%) respectively. Among 140 patients, 115 (82.1%) were living with families and 25 (17.9%) were living alone. Fifty six (40%) patients sustained injuries in early morning, fifty-two (37.1%) in late evening and thirty two (22.9%) in the afternoon. Seventy-three percent subjects fell outside and 26.40% fell inside house. Sixty-five (53.6%) patients were suffering from chronic diseases. Fifty-seven (40.7%) patients were suffering from visual impairment. Fourty-seven (33.6%) patients had multiple joints problem, 20% subjects were anaemic. Hypoglyceaemia was present in fifteen (10.7%) subject. Eighteen (12.9%) subjects had a history of fall in past. Eighteen (12.9%) subject had head injury. Twelve (8.6%) subjects had chest injury. Three (2.1%) subjects had abdominal injury and 24 (17.1%) spinal injury. Seventy-three (52.1%) subjects had fracture, 30 (21.4%) had soft tissue injury, 48 (34.3%) external injury and 11 (7.9%) eye most common injury found in elderly patients in this set up. Mosy of the fall injury injuries. Of all 82 (30.7%) patients were admitted in hospital. Conclusion: Fracture of bone was the occurred outside home. Most of the patients required admission in the hospital for treatment. Health Renaissance 2015;13 (1):